A STUDY OF STRUCTURE CALCULATION AND ELECTRONIC PROPERTIES OF GALLIUM NITRIDE (GaN) DOPED RARE EARTH (Eu, Er, Tm) USING DFT METHOD - ZAHARO (NIM: 20215006), AFLAH
Gallium Nitride (GaN) is a semiconductor that has a direct and wide energy band gap. Research GaN doped Rare Earth (RE) is very interesting related to their use in software development optoelectronics. Performed electronic structure calculations GaN doped with RE is based on the theory of DFT. The model used is supercell wurtzite GaN structure using the program package to PHASE/0. Approximation Exchange Correlation (Exc) used is (Generalized Gradient Approximation) GGA. In this study, the observed stability of RE doped GaN structure and adapted to the experimental data EXAFS. Wurtzite GaN structure stability can be seen from the difference the lattice parameter of about 2% compared to other calculations and experimental results. Seen that a stable structure of wurtzite GaN has the energy gap, Eg, direct bandgaps contained in a hexagonal lattice Γ point of the Brillouin zone. Eg on the structure width of 2.6 eV counted. When done substitution by replacing the Ga atom with one atom RE, resulting in changes in bond length to 11% longer. The configuration used in the structure is Ga(1-x)NMx, where M is the RE and x is posentase RE. There is an impurity energy, EI, which is located relative to the conduction band, Cb, and ribbon valence, Vb. EI diverse width which is influenced by the number of electrons in the subshell 4f. EI width will affect how much energy band gap in the structure of RE in wurtzite GaN. The greater the number of atoms, then the position of Cb and Vb will rise change of the position of pure wurtzite GaN structure. Provision of RE dopants (Eu, Er, Tm) in GaN has produced a variety of primary colors and wavelengths. Combination of two RE (ErTm) to produce a combination of primary colors with a wavelength range between Er and Tm. RE doped GaN has the potential to produce a wide range of LED color with lower energy consumption and cost.